Penyuluhan Gerakan Konsumsi Sayur Dan Buah Bagi Dewasa Tua Dan Lansia Di Kecamatan Ubud Kabupaten Gianyar Tahun 2018 - Desak Putu Sukraniti; I Ketut Kencana; I Made Rodja Suantara (Poltekkes Kemenkes Denpasar, 2019)
Health problems of older adults and the elderly are very important to note, because life expectancy is longer, but on the other hand the emergence of various diseases in older adults and the elderly such as Diabetes Mellitus, Hypertension, Heart Disease, Stroke and other degenerative diseases. On the other hand, patterns of poor eating habits such as frequent consumption of fat, lack of eating vegetables add to the bad health of older adults and the elderly. The Minister of Health in commemoration of National Health Day 2017 invites the Indonesian people to eat vegetables every day which is one of the GERMAS actions. The purpose of Community Service is to find out the knowledge and behavior of vegetable and fruit consumption in elderly and elderly adults in the District of Ubud, Gianyar Regency. The results of dedication are known that there is an increase in knowledge after counseling. Before counseling the average value of target knowledge is 3.7 and after extension the average value of knowledge is 7.2. Before counseling, 61.4% lacked knowledge and 36.4% good knowledge. After knowledge education less decreased to 27.3% and good knowledge increased to 68.2%. The behavior of vegetable and fruit consumption in general is good but not based on good knowledge. Especially the consumption of fruit depends on what is available from what is delivered during prayer.Keywords: Elderly, Consumption, Vegetables and Fruits